(untitled) (Scientific journal of the Fergana State University, 2023)
Modern requirements for the educational process give us the opportunity to accept the organization and formation of professional social competence as a pedagogical process. It is aimed at providing students with high-quality professional competences with the development of significant and motivational spheres and interpersonal and intercultural social competences of professional activity. For this reason, the essence and content of the concept of social competence are studied sociologically and pedagogically in the article. It is also explained that the development of social competence in future specialists is an urgent issue of today, and the analysis of social processes of society is explained using theoretical and methodological approaches.